1993
DOI: 10.1002/ajh.2830420416
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐5 mRNA in three T‐cell lymphomas with eosinophilia

Abstract: The objective of this controlled pilot study was to determine if mRNA coding for interleukin-5 (IL-5), a cytokine that promotes eosinophil differentiation, growth, and migration, could be detected in three T-cell lymphomas that were infiltrated extensively by eosinophils. To detect mRNA coding for IL-5, we performed an RNA polymerase chain reaction on mRNA extracted from three T-cell lymphomas with eosinophilia and from 29 positive and negative validation controls. Using this procedure, we detected a 293-base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…[10], B-ALL (IL-3) [11], Sezary syndrome (IL-5) [12] and T-NHL (IL-5) [13,14], In this study, expression of IL-5 mRNA was not detected in HD ( fig. 3), in which the eosinophilic invasion and eosinophilia were not observed.…”
Section: Discussionmentioning
confidence: 82%
“…[10], B-ALL (IL-3) [11], Sezary syndrome (IL-5) [12] and T-NHL (IL-5) [13,14], In this study, expression of IL-5 mRNA was not detected in HD ( fig. 3), in which the eosinophilic invasion and eosinophilia were not observed.…”
Section: Discussionmentioning
confidence: 82%
“…In malignant lymphoma accompanied by eosinophilia, eosinophilopoietic factors are produced by either malignant cells themselves [15,[17][18][19] or normal MNCs [16]. Our in vitro data indicated that GM-CSF was produced by MNCs from all patients, whereas IL-3 and IL-5 was produced by cells from only one (patient 2).…”
Section: Discussionmentioning
confidence: 56%
“…Several investigators have reported eosinophil-stimulating cytokine involvement in other lymphoid malignancies that are accompanied by eosinophilia. In Hodgkin's disease, for example [13,14], tumor cells [15] or normal MNCs [16] produce IL-5, and T-cell lymphoma cells from patients with eosinophilia secrete different combinations of IL-3, IL-5, and GM-CSF [17,18]. In spite of the high frequency of eosinophilia, the information about its cause in ATL is limited.…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, eosinophils infiltrating interleukin-5, gene-transfected tumors do not suppress tumor growth, 31 and infiltration by eosinophils of natural, interleukin-5-secreting human tumors such as lymphoma is not associated with tumor regression. 11 Finally, we note that the in vitro studies that demonstrated an antitumor cytotoxic effect mediated by eosinophils used exceptionally high ratios of eosinophils to tumor cells (10:1 to 100:1) that probably do not accurately reflect the natural conditions in tumors. 16 Consequently, on the basis of our studies, we conclude that eotaxin is unlikely to elicit an effective anti-tumor response by eosinophils or other inflammatory cells in vivo.…”
Section: Discussionmentioning
confidence: 93%